1999
DOI: 10.1200/jco.1999.17.7.2227
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical/Pharmacokinetic and Pharmacodynamic Trial of the c-raf-1 Antisense Oligonucleotide ISIS 5132 (CGP 69846A)

Abstract: ISIS 5132 is well tolerated at doses up to 6.0 mg/kg when administered as a thrice weekly 2-hour infusion for 3 consecutive weeks. The pharmacokinetic behavior of the drug is reproducible, and suppression of target gene expression is observed in circulating PBMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 24 publications
0
54
0
Order By: Relevance
“…Although studies of Ras transformation using other cell types now indicate that Raf-independent effector function also contributes to Ras transformation (Shields et al 2000), Raf is still generally considered to form the backbone of Ras oncogenesis. The importance of this pathway in Ras transformation is reflected by the current evaluation of anti-Raf and anti-MEK strategies in preclinical and clinical studies (Monia et al 1996;SeboltLeopold et al 1999;Stevenson et al 1999;Cunningham et al 2000;Kloog and Cox 2000;Sebolt-Leopold 2000;Stein and Waterfield 2000). There is also strong evidence for an important supportive role for PI3-kinase in Ras transformation (Rodriguez-Viciana et al 1997;Tolkacheva and Chan 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies of Ras transformation using other cell types now indicate that Raf-independent effector function also contributes to Ras transformation (Shields et al 2000), Raf is still generally considered to form the backbone of Ras oncogenesis. The importance of this pathway in Ras transformation is reflected by the current evaluation of anti-Raf and anti-MEK strategies in preclinical and clinical studies (Monia et al 1996;SeboltLeopold et al 1999;Stevenson et al 1999;Cunningham et al 2000;Kloog and Cox 2000;Sebolt-Leopold 2000;Stein and Waterfield 2000). There is also strong evidence for an important supportive role for PI3-kinase in Ras transformation (Rodriguez-Viciana et al 1997;Tolkacheva and Chan 2000).…”
Section: Discussionmentioning
confidence: 99%
“…132 The antitumor activity of ISIS 5132, a 20-nucleotide phosphorothioate 2 0 deoxynucleotide targeting the 3 0 untranslated region of C-RAF mRNA, was very promising at the early preclinical stage. 133,134 However, no major clinical benefits were observed in several Phase I [135][136][137] or Phase II clinical trials. [138][139][140][141] In addition, the use of ISIS 13650, a second generation antisense oligonucleotide with further modifications in the sugar moiety targeting the same C-RAF sequence as ISIS 5132, has not been superior in certain preclinical settings.…”
Section: Raf Kinases and Cancer Drug Discoverymentioning
confidence: 99%
“…49 Phase I studies in various advanced cancer patients with Raf antisense molecules demonstrated a few patients with prolonged stable disease and one patient with a significant response. [50][51][52] Unfortunately, two phase II studies in lung cancer (total of 26 patients) failed to demonstrate any significant anti-tumor activity. 53 A third set of studies targeted Bcl-2, an apoptotic inhibitor that is overexpressed by many tumors including 80-90% of SCLCs and is associated with increased resistance to chemotherapy.…”
Section: Anti-sense Therapymentioning
confidence: 99%